Does a negative screening colonoscopy ever need to be repeated?. Issue 8 (9th February 2006) - Brenner, H; Chang-Claude, J; Seiler, C M; Stürmer, T; Hoffmeister, M
Abstract : Background and aims: Screening colonoscopy is thought to be a powerful and cost-effective tool to reduce colorectal cancer incidence and mortality. Whether and when colonoscopy with negative findings has to be repeated is not well defined. The aim of this study was to assess the long term risk of clinically manifest colorectal cancer among subjects with negative findings at colonoscopy. Patients: 380 cases and 485 controls participating in a population based case-control study in Germany. Methods: Detailed history and results of previous colonoscopies were obtained by interview and from medical records. Adjusted relative risks of colorectal cancer among subjects with a previous negative colonoscopy compared with those without previous colonoscopy were estimated according to time since colonoscopy. Results: Subjects with previous negative colonoscopy had a 74% lower risk of colorectal cancer than those without previous colonoscopy (adjusted odds ratio (aOR) = 0.26 (95% confidence interval, 0.16 to 0.40)). This low risk was seen even if the colonoscopy had been done up to 20 or more years previously. Particularly low risks were seen for sigma cancer (aOR = 0.13 (0.04 to 0.43)) and for rectal cancer (aOR = 0.19 (0.09 to 0.39)), and after a negative screening colonoscopy at ages 55 to 64 (aOR = 0.17 (0.08 to 0.39)) and older (aOR = 0.21 (0.10 to 0.41)). Conclusions: Subjects with negative findings at colonoscopy are at very low risk of colorectal cancer and might not need to undergo repeat colonoscopy for 20 years or more, if at all. The possibility of extending screening intervals to 20 years or more might reduce complications and increase the feasibility and cost-effectiveness of colonoscopy based screening programmes.